Scarring effects of remaining unemployed for long-term unemployed school-leavers - Bart Cockx; Matteo Picchio (Center for Economic Studies and ifo Institute (CESifo), 2011)
This study investigates whether and to what extent further unemployment experience for youths who are already long-term unemployed imposes a penalty on subsequent labor market outcomes. We propose a flexible method for analyzing the effect on wages aside of transitions from unemployment and employment within a multivariate duration model that controls for selection on observables and unobservables. We find that prolonging unemployment drastically decreases the chances of finding employment, but hardly affects the quality of subsequent employment. The analysis suggests that negative duration dependence in the job finding rate is induced by negative signaling and not by human capital depreciation.
Keywords: C33; C41; J62; J64; 330; scarring effect of unemployment duration; employment quality; wage in multivariate duration model; selectivity; Jugendarbeitslosigkeit; Langzeitarbeitslosigkeit; Berufliche Integration; Lohn; Belgien